2020
DOI: 10.3389/fcvm.2020.00118
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Measurements and Type 2 Diabetes: Investigations in Two Population-Based Cohorts

Abstract: Type 2 diabetes is a major risk factor for cardiovascular disease. Given the contribution of platelets to atherothrombosis-which in turn is a major contributor to cardiac events, there may be cause to consider platelet function in management of diabetes. Despite the large body of research concerning the role of platelets in cardiovascular complications of type 2 diabetes, evidence from population-based studies of platelet aggregation in diabetes is limited. Mean Platelet Volume (MPV), a cell trait partially as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 70 publications
(97 reference statements)
1
19
1
Order By: Relevance
“…It is well known that platelet function changes under diabetic conditions and the risk of thrombotic events is increased. While results from studies in diabetic volunteers are in part controversial [14,15,44], we show here that dapagliflozin affects resting platelets in diabetic mice. However, this is in contrast to healthy humans, in whom an effect was only detectable after agonist stimulation.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…It is well known that platelet function changes under diabetic conditions and the risk of thrombotic events is increased. While results from studies in diabetic volunteers are in part controversial [14,15,44], we show here that dapagliflozin affects resting platelets in diabetic mice. However, this is in contrast to healthy humans, in whom an effect was only detectable after agonist stimulation.…”
Section: Discussioncontrasting
confidence: 49%
“…Clearly, translation to volunteers with diabetes is required in further studies, dapagliflozin decreases thrombin-mediated platelet activation and alpha granule secretion via both direct effects and HDL-mediated effects on thrombin formation. Decreased platelet-leucocyte aggregates and subsequent diminished monocyte-macrophage-recruitment to the vascular wall contribute to atheroprotection by dapagliflozin treatment particularly against the background that clinical studies have shown controversial results regarding platelet activation under diabetic conditions [14,15]. Activated platelets facilitate leucocyte adhesion to the endothelium and subsequent immune cell recruitment to the vascular wall [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several hematological markers have already been reported to be associated with diabetes mellitus. These included red blood cell distribution width (RDW) [ 12 ], mean platelet volume (MPV) [ 13 ], neutrophil count to lymphocyte count ratio (NLR) [ 14 ], platelet count to lymphocyte count ratio (PLR) [ 15 ], and MPV to lymphocyte count ratio (MLR) [ 16 ]. The association between these indicators and diabetes has been well established.…”
Section: Introductionmentioning
confidence: 99%